2017
DOI: 10.1021/acs.nanolett.7b02144
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Optical Magnetism

Abstract: An extension of the Maxwell-Faraday law of electromagnetic induction to optical frequencies requires spatially appropriate materials and optical beams to create resonances and excitations with curl. Here we employ cylindrical vector beams with azimuthal polarization to create electric fields that selectively drive magnetic responses in dielectric core-metal nanoparticle "satellite" nanostructures. These optical frequency magnetic resonances are induced in materials that do not possess spin or orbital angular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 43 publications
2
60
2
Order By: Relevance
“…By contrast, single particle (scattering) measurements of individual metamolecules give sharper spectra, but with significant variation from metamolecule to metamolecule. [ 20 ] Structural characterization by scanning or transmission electron microscopy (SEM or TEM) reveals only partial information about the metamolecule structures. [ 12,15,20 ] Therefore, detailed understanding of the optical properties of core–satellite metamolecules has not been possible to date for three main reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, single particle (scattering) measurements of individual metamolecules give sharper spectra, but with significant variation from metamolecule to metamolecule. [ 20 ] Structural characterization by scanning or transmission electron microscopy (SEM or TEM) reveals only partial information about the metamolecule structures. [ 12,15,20 ] Therefore, detailed understanding of the optical properties of core–satellite metamolecules has not been possible to date for three main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, [ 20 ] single particle scattering spectroscopy measurements were performed using optical vector beams to illuminate individual SiO 2 –Ag nanoparticle core–satellite nanoclusters (metamolecules). We showed that focused vector beams allow selective excitation of collective optical magnetic modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, multi-functional nanomaterials [13,14] have attracted extensive attention from researchers. Nanomaterials [15][16][17][18][19][20][21][22][23] with a single function such as magnetic, [24] conductive [25] or fluorescent characteristics [26,27] are developing towards multifunctional nanomaterids such as with magnetismfluorescence, [28][29][30] fluorescence-conduction, [31,32] conduction-magnetism [33,34] dual-functionality and fluorescence-conductionmagnetism [35,36] tri-functionality. In this way, it is possible to realize double or triple functions in a nanostructured material, which is of great significance for the development of nanoscience and technology.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Manna and co-workers studied optical magnetism in silver (Ag) NP clusters prepared by assembling the NPs on thiol-terminated silica particles. 8 Formation of Au NP cluster shells on coreshell particles with amino-terminated polybutadiene shells and polystyrene cores has also been reported; strong plasmonic coupling and near infrared (NIR) absorption was observed. 9 Thus, three-dimensionally symmetric metal NP clusters have been successfully prepared on spherical particles.…”
mentioning
confidence: 97%